Spatial Structure and Supply Chain Performance: A Comparative Study Across Java - Zahwa Fitria Gumilang; Rose Fatmadewi (UPT Publikasi Ilmiah Unisba, 2026)
Abstract. Supply chain performance of manufacturing companies in developing countries depends on both firm-level strategy and the spatial configuration of the regions in which supply chains operate. In Indonesia, intra-national disparities across Java’s three major industrial provinces including West Java, Central Java, and East Java, create distinct operating environments that are rarely compared through a supply chain management lens. This study introduces an integrative conceptual model linking regional spatial structure to supply chain performance, specifically efficiency, speed, and cost. Drawing on contingency theory, the SCOR model, and perspectives from regional and urban planning, the model operationalizes spatial structure through four dimensions: industrial spatial concentration, logistics infrastructure quality, RTRW zoning compliance, and nodal connectivity. Comparative profiling of these provinces reveals three distinct spatial archetypes, high-concentration, dispersed-SME, and port-centric, each resulting in predictable, differentiated performance outcomes. We advance three propositions: spatial concentration enhances supply chain efficiency, logistics infrastructure quality moderates the strategy–speed relationship, and RTRW non-compliance elevates logistics costs. This interdisciplinary framework bridges supply chain management and regional planning, establishing a roadmap for empirical validation across Java’s manufacturing sectors.